From grid paper to digital e-report: Documentation of handwriting expert examinations (Academic Journal of Internal Affairs, 2022)
Aim: Forensic experts shall keep a report of the examination carried out to establish the origin of the handwriting. The study guides the reader to the author’s own electronic examination report through the temporal changes of the Hungarian handwriting expert reports.Methodology: The electronic report is a software currently under development that provides an interface to explore the characteristics of handwriting and collects the data in a computer database for later analysis.Findings: The stored data can be processed by algorithms, from which mathematical, statistical, probabilistic, and computational results useful to experts can be obtained.Value: The primary task of the e-report is to allow the exploration and recording of handwriting features in a simple and effective way, and secondly, to inform the examining expert about the tendencies, habits, and contexts of handwriting in order to increase the objectivity of handwriting examination.
Keywords: handwriting expertise; identification; features of handwriting; electronic examination report